FEA MEMS Packaging For Sensor - Abdullah@Muhamad, Maswandy (Universiti Sains Malaysia, 2005)
Mechanical characteristics of a sensor microbeam based on resonance frequency for gas detection and their dependence on the geometry and materials is investigated in this paper. These microbeam structures will be modeled in Finite Element Analysis software (ANSYS 7.0). The microbeam structures investigated in this work are formed from six microcantilevers and a microbridge design. Each of the microcantilevers has differences in their dimensions. While the microbridge will be analyzed in different materials. All of six microcantilevers also will be analyzed in these different materials to define the best result. Each of these structures has a specific resonance frequency, which varies as a function device shape, structure mass and the physical properties of its component materials. The microbeam structures are then will be simulating in ANSYS 7.0 software to measure its resonance frequencies value. Parametric studies for the microcantilever also will be investigated. Preliminary results shows the shorter microcantilever have higher resonance frequency than the longer ones using polysilicon material, and silicon nitride material give the higher resonance frequency modes for microbeam structure design than other materials. These results will be verified with experimental result in journal. The packaging technique also will be applied to this sensor depends on its requirements and applications. This packaging technique will be discussed roughly in this paper.